Heritability of decisions and outcomes of public goods games - Hiraishi, Kai; Shikishima, Chizuru; Yamagata, Shinji; Ando, Juko (Frontiers in Psychology, 2015)
Prosociality is one of the most distinctive features of human beings but there are individual differences in cooperative behavior. Employing the twin method, we examined the heritability of cooperativeness and its outcomes on public goods games using a strategy method. In two experiments (Study 1 and Study 2), twin participants were asked to indicate (1) how much they would contribute to a group when they did not know how much the other group members were contributing, and (2) how much they would contribute if they knew the contributions of others. Overall, the heritability estimates were relatively small for each type of decision, but heritability was greater when participants knew that the others had made larger contributions. Using registered decisions in Study 2, we conducted seven Monte Carlo simulations to examine genetic and environmental influences on the expected game payoffs. For the simulated one-shot game, the heritability estimates were small, comparable to those of game decisions. For the simulated iterated games, we found that the genetic influences first decreased, then increased as the numbers of iterations grew. The implication for the evolution of individual differences in prosociality is discussed.